DIFFERENTIAL DISEASE REACTION OF RICE PATHOGEN XANTHOMONAS ORYZAE PV. ORYZAE PREVAILING IN INDIA ON RICE CULTIVARS - S. BHARATHKUMAR; S. S. GNANAMANICKAM; K. JITENDRA; B. ARCHANA; B. SK. YASIN; D. AMIT; K. N. DEEPAK (The Bioscan, 2014)
In the present study, the virulence of Xanthomonas oryzae pv. oryzae (Xoo) causing bacterial blight disease in rice was analyzed using 200 isolates of Xoo on near isogenic lines (NILs) and rice differentials having single or different gene combinations at field condition. These isolates were assembled from major rice growing areas of Punjab, Haryana, Uttar Pradesh, Bihar, West Bengal, Odisha, Andhra Pradesh, Tamilnadu and Kerala state. From these isolates, 20 pathotypes (races) on NILs and 12 pathotypes on rice differentials were identified based on disease reaction. In this analysis, more number of pathotypes were identified in Bihar state (10 pathotypes) followed by Uttar Pradesh (7 pathotypes), Haryana, West Bengal, Andhra Pradesh, Kerala (6 pathotypes), Odisha (4 pathotypes), Punjab (3 pathotypes) and Tamilnadu (2 pathotypes). Among these, pathotype I was virulent to all rice cultivar harbouring single resistant gene (Xa4, xa5, Xa7, Xa10 and xa13) and it was found to be prevalent throughout India. Significantly, isolates of pathotype III prevailing in Haryana state were noted that they breakdown the resistance of IRBB21 (Xa21) and IRBB52 (Xa4+Xa21). Thus, in this analysis, data clearly is revealed that almost all the isolates were able to overcome only those NILs which harbored a single resistant gene (i.e. IRRB4) or two gene (i.e. IRBB52/DV85) for BB resistance and not those NILs (i.e. IRBB57-IRBB60) which harbored either a 3-gene/4-gene combinations.